Generation of therapeutic antisera for emerging viral infections. (December 2018) - Schmidt, Rebecca; Beltzig, Lea; Sawatsky, Bevan; Dolnik, Olga; Dietzel, Erik; Krähling, Verena; Volz, Asisa; Sutter, Gerd; Becker, Stephan; von Messling, Veronika
Abstract The recent Ebola virus outbreak has highlighted the therapeutic potential of antisera and renewed interest in this treatment approach. While human convalescent sera may not be readily available in the early stages of an outbreak, antisera of animal origin can be produced in a short time frame. Here, we compared adjuvanted virus-like particles (VLP) with recombinant modified vaccinia virus Ankara and vesicular stomatitis virus (VSV), both expressing the Ebola virus antigens. The neutralizing antibody titers of rabbits immunized with adjuvanted VLPs were similar to those immunized with the replication-competent VSV, indicating that presentation of the antigen in its native conformation rather than de novo antigen expression is essential for production of functional antibodies. This approach also yielded high-titer antisera against Nipah virus glycoproteins, illustrating that it is transferable to other virus families. Multiple-step immunoglobulin G purification using a two-step 20–40% ammonium sulfate precipitation followed by protein A affinity chromatography resulted in 90% recovery of functionality and sustained in vivo stability. Adjuvanted VLP-based immunization strategies are thus a promising approach for the rapid generation of therapeutic antisera against emerging infections. Anti-serum: Rapid generation for viral outbreaks Passive immunity through the transfer of anti-serum represents the earliest clinical application of antibodies and is still widely used to this day in the form of anti-venoms. Veronika von Messling and colleagues at the Paul Ehrlich Institute investigate the potential of generating neutralizing anti-serum to the emerging viruses Ebola and Nipah. The authors compare different vaccination platforms in mice and rabbits and find that following multiple vaccine challenges, neutralizing antibody titers equivalent to that seen in convalescent patients could be obtained. Purification of the IgG fraction and processing into F(ab')2 fragments has the potential to significantly reduce xeno-responses yet the authors find that neutralizing capacity is largely retained albeit at the cost of a shorterin vivo half-life. These findings offer the hope of rapidly generating large quantities of neutralizing anti-serum that could be used in a viral outbreak scenario.